Effectiveness of the Use of Birth Plan in Hong Kong Chinese Women: a Qualitative Exploratory Research - Sham, A; Chan, L; Yiu, KL; Ng, CW; Ng, J; Tang, PL (Hong Kong Journal of Gynaecology, Obstetrics and Midwifery, 2023)
A qualitative research using focus group interviews was carried out to explore the perceptions of Hong Kong Chinese women and investigate the effectiveness of the use of the preset birth plan. The findings revealed that birth plan was a new idea to them. The content of the preset birth plan was simple and clear. It was easy to understand and use. Its use was especially beneficial to the primiparae in the aspects of self-preparation and communication with midwife. It enabled them to make their own choices. It could act as a guideline or reminder of the labour process.